1994
DOI: 10.1111/j.1600-0609.1994.tb00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine sulfate for the treatment of thrombotic thrombocytopenic purpura refractory to plasma‐exchange

Abstract: Among all the patients treated by the Italian Cooperative Group for TTP, we retrospectively reviewed the results obtained using vincristine (VCR) in 8 TTP patients (4 men and 4 women, average age: 39.25 years, range: 23–48) who did not respond to combined apheretic and pharmacologic treatment. All patients, after failing to respond to treatment, were started on VCR at the dose of 2 mg, i.v., once a week. Despite this treatment, 4 patients (50%) died 1, 7, 12 and 25 days after the first VCR dose, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Successful vincristine use has been described in various small studies and case reports, usually as a rescue therapy in refractory TTP [17,[24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the 1980s, 3 patients with chronic TTP were described as having very low levels of a serum prostacyclin-binding activity, 33 which was later identified as ApoA-I. 34 Although treatment of plasmapheresis-resistant TTP patients with prostacyclin homologs was unsuccessful, 35 the association of low ApoA-I levels with TTP has not been explained; our results suggest that the reduced ApoA-I levels in patients with TTP and sepsis may worsen these disorders. Replenishment of HDL may contribute to the effectiveness of plasmapheresis in the treatment of TTP in addition to providing ADAMTS13 and For personal use only.…”
Section: Discussionmentioning
confidence: 83%
“…[59][60][61] The side-effect profile includes mild peripheral paresthesias, muscle weakness, paralytic ileus, leukopenia, and transient alopecia. 62 Vincristine may work better when used in the initial treatment of patients with TTP, rather than for treating refractory patients.…”
Section: Cyclophosphamide and Vincristinementioning
confidence: 99%